2002
DOI: 10.2337/diacare.25.5.883
|View full text |Cite
|
Sign up to set email alerts
|

Improved Postprandial Glycemic Control With Biphasic Insulin Aspart Relative to Biphasic Insulin Lispro and Biphasic Human Insulin in Patients With Type 2 Diabetes

Abstract: OBJECTIVE—The rapid-acting insulin analogs aspart and lispro have now been developed in biphasic formulations. This trial compared the postprandial serum glucose control of biphasic insulin aspart 30 (BIAsp 30: 30% aspart, 70% protaminated aspart) with that of biphasic insulin lispro 25 (Mix25: 25% lispro, 75% protaminated lispro) and biphasic human insulin 30 (BHI 30: 30% regular insulin, 70% NPH insulin) in insulin-treated subjects with type 2 diabetes. RESEARCH DESIGN AND METHODS—This was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 25 publications
6
68
1
2
Order By: Relevance
“…Postprandial hyperglycaemia is acknowledged as an inde- pendent risk factor for macrovascular disease and mortality [13,14]. The results from the present study suggest that postprandial glucose excursions in people with type 2 diabetes would be more effectively controlled with BIAsp 30 than with the basal insulin IGlarg when given as monotherapy unsupported by OHAs with secretagogue properties [9]. In clinical practice, however, IGlarg is normally added to OHAs when these preparations, either as monotherapy or combination therapy, have failed to achieve the desired glycaemic targets.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Postprandial hyperglycaemia is acknowledged as an inde- pendent risk factor for macrovascular disease and mortality [13,14]. The results from the present study suggest that postprandial glucose excursions in people with type 2 diabetes would be more effectively controlled with BIAsp 30 than with the basal insulin IGlarg when given as monotherapy unsupported by OHAs with secretagogue properties [9]. In clinical practice, however, IGlarg is normally added to OHAs when these preparations, either as monotherapy or combination therapy, have failed to achieve the desired glycaemic targets.…”
Section: Discussionmentioning
confidence: 69%
“…Plasma insulin rose rapidly after each injection of BIAsp 30, reaching a peak within 2-3 h after injection. In this way, BIAsp 30 approached the desired serum insulin profile for the purpose of controlling postprandial glucose [9]. However following the rapid increase in plasma insulin there was a slow decline towards baseline because of the intermediate-acting, protaminated IAsp component.…”
Section: Discussionmentioning
confidence: 97%
“…• Insulin aspart 70/30 versus insulin lispro 75/25-2 randomized crossover studies 37,59 • Insulin lispro 75/25 versus insulin lispro 50/50-1 randomized crossover study 41 • Insulin lispro 75/25 versus morning insulin lispro 50/50 plus dinner insulin lispro 75/25-1 randomized crossover study 60 No treatment-group differences were observed for changes in fasting blood glucose. However, 2 studies indicated that postprandial glucose concentration was reduced to a greater extent in patients treated with insulin lispro 50/50 than with insulin lispro 75/25 (P < 0.05 and P = 0.001, respectively).…”
Section: Comparisons Among Premixed Insulin Analoguesmentioning
confidence: 99%
“…• Insulin aspart 70/30 versus NPH/regular 70/30-3 parallel-arm trials 31,33,34 and 3 crossover trials [35][36][37] • Insulin lispro 75/25 versus NPH/regular 70/30 or NPH/regular 50/50-9 randomized crossover studies [37][38][39][40][41][42][43][44][45] and 1 retrospective observational study 28 • Insulin lispro 50/50 versus NPH/regular 70/30 or NPH/ regular 50/50-3 randomized crossover studies 38,41,46 and 1 parallel-arm study 47 The studies varied considerably in therapy administration methods, dosing schedules, and duration.…”
Section: Premixed Insulin Analogues Versus Premixed Human Insulinmentioning
confidence: 99%
“…At the time, we chose biphasic insulin aspart 30 as the comparator insulin because a pharmacodynamic assessment following a test meal indicated lower serum glucose excursions with biphasic insulin aspart 30 compared with biphasic human insulin 30 and Mix25 [8]. Since improved postprandial glucose is an important glucoregulatory attribute of exenatide, we did not want to disadvantage the insulin arm in any way.…”
mentioning
confidence: 99%